La vivienda palafítica como identidad tipológica, arquitectónica y urbanística en la isla de Cascajal de la ciudad de Buenaventura. (2022)
For many years, regional identity has manifested itself through its population, its culture, idiosyncrasy, gastronomy and different elements that identify a place. the pacific coast Colombia specifically in the district of Buenaventura is not the exception of these acknowledgments; and it is through architecture that reflects the history of a territory and its society, through the stilt houses; a typology that has transcended for decades as a symbol identity, teaching and empiricism of our ancestors.